Experimental Study of the Effect of Blade Shape on the Performance of Darrieus Turbines. - Sinaga, jorfri Boike (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2024)
This paper presents an experimental study on the effects of blade shape on the performance of a straight-bladed hydrokinetic turbine of the Darrieus type. The blade shapes used are RISO A-832, NACA 63-818, and NREL S833. The tested turbine has a diameter of 20 cm, a height of 20 cm, a chord length of 8.3 cm, and three blades. Testing was conducted with variations in flow rates of 0.064 m3/s, 0.008 m3/s , and 0.094 m3/s . The test results show that the maximum efficiency of 20.53 % achieved by the RISO A-832 blade shape is better compared to the NACA 63-818 and NREL S833 blade shapes, which yielded maximum efficiencies of 17.31 % and 14.29 %, respectively, at a flow rate of 0.094 m3/s .